Influence of Local Pressures on Maldivian Coral Reef Resilience Following Repeated Bleaching Events, and Recovery Perspectives - Montefalcone, Monica; Morri, Carla; Bianchi, Carlo Nike (Frontiers in Marine Science, 2020)
Two severe heat waves triggered coral bleaching and mass mortality in the Maldives in 1998 and 2016. Analysis of live coral cover data from 1997 to 2019 in shallow (5 m depth) reefs of the Maldives showed that the 1998 heat wave caused more than 90% of coral mortality leaving only 6.8±0.3% of survived corals in all the shallow reefs investigated. No significant difference in coral mortality was observed among atolls with different levels of human pressure. Maldivian reefs needed sixteen years to recover to the pre-bleaching hard coral cover values. The 2016 heat wave affected all reefs investigated, but reefs in atolls with higher human pressure showed greater coral mortality than reefs in atolls with lower human pressure. Additionally, exposed (ocean) reefs showed lower coral mortality than those in sheltered (lagoon) reefs. The reduced coral mortality in 2016 as compared to 1998 may provide some support to the Adaptive Bleaching Hypothesis (ABH) in shallow Maldivian reefs, but intensity and duration of the two heat waves were different. Analysis of coral cover data collected along depth profiles on the ocean sides of atolls, from 10 m to 50 m, allowed the comparison of coral mortality at different depths to discuss the Deep Refuge Hypothesis (DRH). In the upper mesophotic zone (i.e., between 30 and 50 m), coral mortality after bleaching was negligible. However, live coral cover did not exceed 15%, a value lower than coral survival in shallow reefs. Low cover values of corals surviving in the mesophotic reefs suggest that their role as refuge or seed banks for the future recovery of some species in shallow-water reefs of the Maldives may be small. The repeatedly high coral mortality after bleaching events and the long recovery period, especially in sites with human pressure, suggest that the foreseen increased frequency of bleaching events would jeopardize the future of Maldivian reefs, and ask for reducing local pressures to improve their resilience.